Social and gender perspectives in rice breeding for submergence tolerance in Southeast Asia - Manzanilla, D.O.; Paris, T.R.; Tatlonghari, G.T.; Tobias, A.M.; Chi, T. T. N.; Phuong, N.T.; Siliphouthone, I.; Chamarerk, V.; Bhekasut, P.; Gandasoemita, R. (Cambridge University Press, 2014)
The risks of flooding in rice production include losses that can affect some 13 million ha of rice lands in Southeast Asia. This study integrated social and gender perspectives into the varietal evaluation process to contribute to planned faster uptake of submergence-tolerant rice (Sub1) varieties. In this study, the participatory varietal selection (PVS) process was used in eliciting male and female farmers' opinions with respect to selecting popular varieties with the SUB1 gene introgressed, for added tolerance of flash floods of up to two weeks. Fifteen Sub1 varieties and the farmers' local check were tested under the PVS researcher-managed (PVS-RM) trials, which involved farmers' preference analysis (PA). The farmers tested the pre-selected lines with the SUB1 gene in their own fields to further evaluate their performance under varying conditions. During flooding, farmers experienced lower production depending on water depth, timing with respect to rice growth stage, duration, frequency of occurrence and quality. On-farm PA results showed wide variability in the performance of the Sub1 varieties compared with local popular varieties. This implies the need for further testing of pre-released lines in terms of adaptability and the continuous development of rice genotypes for varying flood-prone rice ecosystems. Women are as knowledgeable as men because of the significant roles they play in rice production and food preparation. Moreover, farmers and breeders have almost the same criteria in choosing the best performing rice lines. Sensory tests revealed the eating and cooking qualities important to farmers. The findings of this study can provide feedback to breeding programmes to ensure a greater likelihood of adoption and ultimately increasing rice productivity in submergence-prone rice areas.